2017
DOI: 10.3389/fncel.2017.00311
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbation of Brain Injury by Post-Stroke Exercise Is Contingent Upon Exercise Initiation Timing

Abstract: Accumulating evidence has demonstrated that post-stroke physical rehabilitation may reduce morbidity. The effectiveness of post-stroke exercise, however, appears to be contingent upon exercise initiation. This study assessed the hypothesis that very early exercise exacerbates brain injury, induces reactive oxygen species (ROS) generation, and promotes energy failure. A total of 230 adult male Sprague-Dawley rats were subjected to middle cerebral artery (MCA) occlusion for 2 h, and randomized into eight groups,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 51 publications
5
36
0
Order By: Relevance
“…Specifically, we showed that both mild and intense exercise regimens reduced brain infarct volume and apoptotic cell death, and improved motor and cognitive function at 3, 14, and 28 days after ischemia/reperfusion injury. The early improvement in infarct volume seen in these results aligned with a previous meta-analysis, in which infarct volume was reduced most effectively by exercise administered with the shortest delays after ischemia (Egan et al, 2014 ); data from our group derived from pre-conditioning experimentation suggest that this may be related to the capacity of exercise to mitigate inflammatory damage during reperfusion (Ding et al, 2005 ), with the caveat that the exercise initiation too early after ischemia may be detrimental (Li et al, 2017a ). More recent work by our group further substantiated these findings by demonstrating that exercise improved glycometabolism in the ischemic area and decreased neuroinflammation and apoptosis as early as 1 day post-stroke, and also at 3 days (Shen et al, 2016 ; Li et al, 2017a , b , c ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically, we showed that both mild and intense exercise regimens reduced brain infarct volume and apoptotic cell death, and improved motor and cognitive function at 3, 14, and 28 days after ischemia/reperfusion injury. The early improvement in infarct volume seen in these results aligned with a previous meta-analysis, in which infarct volume was reduced most effectively by exercise administered with the shortest delays after ischemia (Egan et al, 2014 ); data from our group derived from pre-conditioning experimentation suggest that this may be related to the capacity of exercise to mitigate inflammatory damage during reperfusion (Ding et al, 2005 ), with the caveat that the exercise initiation too early after ischemia may be detrimental (Li et al, 2017a ). More recent work by our group further substantiated these findings by demonstrating that exercise improved glycometabolism in the ischemic area and decreased neuroinflammation and apoptosis as early as 1 day post-stroke, and also at 3 days (Shen et al, 2016 ; Li et al, 2017a , b , c ).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we intended to observe the protective effects of post-stroke exercise on brain infarct at 3 days as previous studies did. Recent work by our group substantiates these findings by demonstrating exercise-improved glycometabolism, decreased neuroinflammation, and apoptosis (Li et al, 2017a , b , c ). The present results were largely supported by the findings of other groups, which demonstrated that exercise accelerated CBF (Pianta et al, 2019 ), decreased infarct volume (Tian et al, 2013 ; Zhang Y. et al, 2013 ; Pan et al, 2020 ) and improved functional outcomes (Pianta et al, 2019 ).…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The early imbalance in interhemispheric connectivity following stroke ( Figure 1 ) suggested us a prompt inactivation of the contralesional cortex via BoNT/E, which requires at least 24 hr to become fully active ( Antonucci et al, 2008 ). For robotic training, we chose to start the physiotherapy at day 5, since it is known that early exercise may exacerbate brain injury, via excitotoxicity and generation of reactive oxygen species ( Kozlowski et al, 1996 ; Li et al, 2017 ). Moreover, it is widely believed that priming the brain with a ‘plasticity-stimulating’ treatment before the beginning of a rehabilitative treatment improves motor performance after brain lesions ( Schäbitz et al, 2004 ; Starkey et al, 2012 ; Wahl et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Defining and identifying this association is the first step in further investigating if the repletion of VitB1 in these patients during their continuum of care may play a role in optimizing their recovery. This latter point may be most important given the increased metabolic demands of the brain at baseline and especially post-stroke [45], similar to the increased metabolic demand seen in the VitB1 deficiency of chronic alcoholics [46]. The increased metabolic demand post-stroke was observed as early as the 1970s by investigators reporting an increase of up to 100% in energy requirements of patients with hemiparetic gait [47,48].…”
Section: Vitb1 and Strokementioning
confidence: 99%